Spiritualitas Kerja dalam Islam dan Kapitalisme Etis - Sumarta, Sumarta; Maulana, Yana Hidayat; Hermawan, Muhamad Ibnu (Jurnal Inovasi Global, 2025)
Work spirituality is an important aspect of professional life that can influence productivity and job satisfaction. In the Islamic context, work spirituality focuses not only on material achievement but also on ethical and moral values. This journal discusses the relationship between work spirituality in Islam and the principles of ethical capitalism, as well as its implications for the modern workplace. Through this research, it is hoped that a synergy between spiritual values and ethical business practices can be found.